Network embeddedness, entrepreneurial bricolage, and family farm sustainability - Duan, Haixia; Wang, Zhaochen; Yi, Zhaohui; Su, Xiaohua (Frontiers in Sustainable Food Systems, 2024)
Family farm sustainability is an essential guarantee for increasing the resilience of food systems. Based on the network embeddedness theory and entrepreneurial bricolage theory, an exploratory longitudinal case study was adopted. The value-creating behaviors of family farms in different entrepreneurial periods were described and a process model of family farms sustainability with network embeddedness and entrepreneurial bricolage was constructed. The study revealed that family farms faced resource constraints such as shortage of element resources, insufficient market resources and lack of knowledge resources during the induction, start-up, and growth periods, respectively. In order to overcome resource constraints in different entrepreneurial periods, family farms employed multiple network embeddedness ways including relational embeddedness, structural embeddedness and cognitive embeddedness to seek help from actors in the rural social network. Family farms embedded in multiple networks used the entrepreneurial bricolage strategy of “element bricolage – market bricolage – institutional bricolage” to continuously acquire production elements, improve brand awareness, optimize processing techniques and promote the convergence of three industries. Family farms benefited from a win-win result with actors through network embeddedness and entrepreneurial bricolage, and created economic, social and ecological values eventually. The study offers fresh insights into the dynamics of rural entrepreneurship.